2021
DOI: 10.3390/metabo11050273
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Uses Host Lipids to Its Own Advantage

Abstract: Lipids and lipoproteins constitute indispensable components for living not only for humans. In the case of hepatitis C virus (HCV), the option of using the products of our lipid metabolism is “to be, or not to be”. On the other hand, HCV infection, which is the main cause of chronic hepatitis, cirrhosis and hepatocellular carcinoma, exerts a profound influence on lipid and lipoprotein metabolism of the host. The consequences of this alternation are frequently observed as hypolipidemia and hepatic steatosis in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 121 publications
(148 reference statements)
0
26
0
Order By: Relevance
“…Results showed that the overall changes in CAP were significantly elevated at SVR24; moreover, these changes were negatively correlated with baseline values of steatosis, whereby, in patients with severe steatosis at baseline, CAP values were decreased while those with lower baseline of steatosis experienced elevation of CAP. Since the impairment of VLDL secretion as a result of downregulation of MTP has been known to cause hypocholesterolemia and decreased triglyceride levels in HCV patients [114], successful treatment with DAAs might lead to elevation of LDL-C and triglycerides [115,116]. A summary of the response to IFN-based and IFN-free DAAs in HCV-associated steatosis is illustrated in Figure 4.…”
Section: The Impact Of Antiviral Therapy On Hcv-related Steatosis Extrahepatic Manifestations and Hccmentioning
confidence: 99%
“…Results showed that the overall changes in CAP were significantly elevated at SVR24; moreover, these changes were negatively correlated with baseline values of steatosis, whereby, in patients with severe steatosis at baseline, CAP values were decreased while those with lower baseline of steatosis experienced elevation of CAP. Since the impairment of VLDL secretion as a result of downregulation of MTP has been known to cause hypocholesterolemia and decreased triglyceride levels in HCV patients [114], successful treatment with DAAs might lead to elevation of LDL-C and triglycerides [115,116]. A summary of the response to IFN-based and IFN-free DAAs in HCV-associated steatosis is illustrated in Figure 4.…”
Section: The Impact Of Antiviral Therapy On Hcv-related Steatosis Extrahepatic Manifestations and Hccmentioning
confidence: 99%
“…Consequently, hypolipidemia and hepatic steatosis are conditions frequently occurring in chronic hepatitis C patients. These metabolic changes in host highlight the close interplay between HCV and the lipid metabolism, with lipids and lipoproteins playing a crucial role in the virus lifecycle [ 45 ]. A strict relationship between lipids and HCV is necessary for the mechanism of viral entry into hepatocytes, replication, particles assembly and secretion [ 46 ].…”
Section: Changes In Lipid Metabolism During Sars-cov2 Hcv and Hcmv Infectionmentioning
confidence: 99%
“…HCV core protein was reported to interact with host lipid droplets, thus dysregulating lipid turnover and promoting LVP assembly [12,13]. Additionally, HCV infection induces the activation of Sterol Regulatory Element-Binding Protein (SREBP), the transcription factor responsible for lipogenesis [14,15]. Downregulation of carnitine palmitoyltransferase expression may additionally increase steatosis by inhibition of beta-oxidation [16].…”
Section: Introductionmentioning
confidence: 99%
“…These observations highlight the necessity for HCV to interfere with lipid metabolism but the lack of a metabolically competent cell line mimicking hepatic lipogenesis and lipoprotein synthesis has significantly hampered our understanding of this phenomenon [8,15,19,21]. Indeed, the in vitro assembly of bona fide infectious LVPs was only observed in primary human hepatocytes that are functional for the production of very low-density lipoproteins (VLDLs).…”
Section: Introductionmentioning
confidence: 99%